PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII MTs NEGERI RAMBAH - Junaidi, Tri; Deswita, Hera; -, Arcat (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The purpose of the research was to know the effect of Student Teams Achievement Division (STAD) cooperative learning model on the results of students mathematics learning. The population of this research was class VIII MTs Negeri Rambah. The technique of sampling was done by simple random sampling. The sample of this research was class VIII4 as an experimental class and class VIII7 as class of control. By the test of normality and homogeneity tests showed that two samples ware normally distributed and homogeneous. Analysis of the data using the t test with Î± = 0.05 indicates tcoun=2.436 and ttable= 1.99, tcount> ttable so that H0 was rejected. So it can be concluded that there was significant STAD cooperative learning model for students mathematics learning outcomes